Histopathological spectrum of common aldosterone-driver gene mutations in aldosterone-producing adenomas - Fatin Athirah Pauzi; Muaatamarulain Mustangin; Geok Chin Tan; Ales Ryska; Jiri Ceral; Miroslav Solar; Elena Aisha Azizan (Frontiers in Medicine)
Past studies on common mutant aldosterone-producing adenomas (APAs) had found genotype–phenotype correlations associated with histological appearance. Most of these studies did not perform CYP11B2-guided sequencing of APAs or sequencing for all the currently known aldosterone-driver genes. Hence, misinterpretation of the genotype–phenotype correlations could have occurred. Herein, we aimed to identify the genotype–phenotype correlations associated with the histopathology of the different mutant APAs utilizing CYP11B2-guided sequencing. A total of 33 APAs with confirmed aldosterone-driver mutation (17 KCNJ5 mutant APAs, 8 ATP1A1 mutant APAs, 6 CACNA1D mutant APAs, and 2 CTNNB1 mutant APAs) were immunohistochemically stained using H&E, CYP17A1, CYP11B2, KCNJ5, Ki67, β-catenin, and LHCGR antibody. Interestingly, APAs with a p.Thr41Ala CTNNB1 mutation also harbored a p.Val1373Met CACNA1D mutation. The CTNNB1 double mutant APAs had less expression of CYP17A1 and larger quantities of spironolactone bodies than a single mutant APA with a p.Ser45Phe CTNNB1 mutation. However, both CTNNB1 mutant APAs displayed diffuse active β-catenin expression with prominent nuclear staining that reflects the constitutive activation of the Wnt/β-catenin signaling pathway (p = 0.016 compared to other genotypes) but no significant increase in LHCGR. KCNJ5 mutant APAs displayed distinct existence of atypical cells (6 of the 17 KCNJ5 mutant APAs), whereas CACNA1D mutant APAs had frequent presentations of spironolactone bodies (4 of the 6 CACNA1D mutant APAs), and ATP1A1 mutant APAs had significantly higher Ki67 score than KCNJ5 mutant APAs (p = 0.020). The results of this study support the notion that CYP11B2-guided sequencing of all currently known aldosterone-driver genes can fine-tune existing genotype–phenotype correlations in histopathological profiles.